Process evaluation of a community-based intervention promoting multiple maternal and neonatal care practices in rural Nepal - McPherson, Robert A (BioMed Central, 2010)
BACKGROUND: The challenge of delivering multiple, complex messages to promote maternal and newborn health in the terai region of Nepal was addressed through training Female Community Health Volunteers (FCHVs) to counsel pregnant women and their families using a flipchart and a pictorial booklet that was distributed to clients. The booklet consists of illustrated messages presented on postcard-sized laminated cards that are joined by a ring. Pregnant women were encouraged to discuss booklet content with their families. METHODS: We examined use of the booklet and factors affecting adoption of practices through semi-structured interviews with district and community-level government health personnel, staff from the Nepal Family Health Program, FCHVs, recently delivered women and their husbands and mothers-in-law. RESULTS: The booklet is shared among household members, promotes discussion, and is referred to when questions arise or during emergencies. Booklet cards on danger signs and nutritious foods are particularly well-received. Cards on family planning and certain aspects of birth preparedness generate less interest. Husbands and mothers-in-law control decision-making for maternal and newborn care-seeking and related household-level behaviors. CONCLUSIONS: Interpersonal peer communication through trusted community-level volunteers is an acceptable primary strategy in Nepal for promotion of household-level behaviors. The content and number of messages should be simplified or streamlined before being scaled-up to minimize intervention complexity and redundant communication.